2023
DOI: 10.1111/odi.14587
|View full text |Cite
|
Sign up to set email alerts
|

Textbook outcome was associated with better survival in oral cancer surgery in southern Taiwan

Abstract: ObjectiveTo explore the impact of textbook outcome (TO) on long‐term survival in oral cancer surgery.Subjects and MethodsIn total, 386 patients with tumor resection, neck dissection (ND), and reconstruction between 2011 and 2020 were included. TO was defined as negative margin; adequate ND; no 3‐day emergency room revisit; no 30‐day readmission; and length of stay ≤22 days. Multivariate Cox regression was used to evaluate the impact of TO and 5‐year overall survival (OS).ResultsThe TO rate was 35%. Younger age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…There has been limited research in assessing the role of TO in head and neck cancers so far. In a recently published study from Taiwan (Chiou & Lee, 2023), the authors reported that the TO rate was 35% and the patients who achieved TO had a higher 5-year overall survival rate (70.5%) compared to non-TO patients (49.0%).…”
Section: Comment On: Textbook Outcome Was Associated With Better Surv...mentioning
confidence: 99%
“…There has been limited research in assessing the role of TO in head and neck cancers so far. In a recently published study from Taiwan (Chiou & Lee, 2023), the authors reported that the TO rate was 35% and the patients who achieved TO had a higher 5-year overall survival rate (70.5%) compared to non-TO patients (49.0%).…”
Section: Comment On: Textbook Outcome Was Associated With Better Surv...mentioning
confidence: 99%